Business Development of Air Tebu (Sugarcane Water) in Sungai Alam Village - kartika alfira; Adrian Irnanda Pratama (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
The purpose of this final project is to develop this business by creating product diversification, business branding, packaging, new booths, logos, Standard Operating   Procedures   (SOP),   marketing   mix,   constraints   and   solutions encountered during the implementation of this final project to increasing income. This final project uses 3 methods consisting of a project preparation plan, project implementation plan and project accomplishment plan. The results of the implementation of this final project are diversified products in the form of Kasturi Sugarcane and Ginger Sugarcane, a business brand in the form of "Es Tebu Pak De Ren", the packaging using PP injection Cup 500 ml, new booths with wood and aluminum materials, logos with Letter Mark Only type, setting the Standard Operating Procedure (SOP) for production and service, marketing mix using the 4P method: Products in the form of Tebu Jahe and Tebu Kasturi, pricing using the cost plus pricing method of variable costing approach, promotion using social media (Whatsapp, Facebook and Instagram), location marketing in Sungai Alam Village. The obstacles faced during the implementation of the project were the weather conditions and running out of packaging supplies, the solution was to pay attention to the weather conditions first and use a replacement cup in the form of a 16 oz plastic cup. The implementation of this final project will start from October 1 to November 25, 2022.